Thinopyrum 7Ai-1-derived small chromatin with Barley Yellow Dwarf Virus (BYDV) resistance gene integrated into the wheat genome with retrotransposon - Ma, Y.-Z.; Tomita, M. (Цитология и генетика, 2013)
Thinopyrum intermedium is a useful source of resistance genes for Barley Yellow Dwarf Virus (BYDV), one of the most damaging wheat diseases. In this study, wheat/Th. intermedium translocation lines with a BYDV resistance gene were developed using the Th. intermedium 7Ai-1 chromosome. Genomic in situ hybridization (GISH), using a Th. intermedium total genomic DNA probe, enabled detection of 7Ai-1-derived small chromatins containing a BYDV resistance gene, which were translocated onto the end of wheat chromosomes in the lines Y95011 and Y960843. Random amplified polymorphic DNA (RAPD) analyses using 120 random 10-mer primers were conducted to compare the BYDVresistant translocation lines with susceptible lines. Two primers amplified the DNA fragments specific to the resistant line that would be useful as molecular markers to identify 7Ai-1-derived BYDV resistance chromatin in the wheat genome. Additionally, the isolated Th. intermedium-specific retrotransposon-like sequence pTi28 can be used to identify Th. intermedium chromatin transferred to the wheat genome.